ChatGPT: Between Opportunities and Challanges in Increasing Academic Productivity - Binti Rohaizam, Nursuhaida (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2024)
Introduction: CHATGPT, one of Open AI's successful new innovations, has amazed people all over the world. ChatGPT helps scientific research in learning can be a beneficial educational innovation for students and higher education but also has promising potential and threats. Purpose: This research will provide an overview of the opportunities and challenges of using ChatGPT for students. Method: Literature Study, a qualitative approach. Finding: The main challenges and ethical implications of ChatGPT in higher education :1. Academic Integrity 2. Gender and Diversity 3. Accessibility. Navigating the Digital Shift: Enhancing Digital Competency in Education. Human-AI collaboration and advanced technology pedagogy: an opportunity for ChatGPT. Conclusion: ChatGPT can be used in higher education and training, to (i) assign individualized teaching resources and study plans based on each learner's needs and interests, (ii) guide learners through their education in a timely manner, (iii) produce learning materials that interesting things such as tests, interesting assignments, and interactive videos, (iv) supporting lecturers in evaluating student work and providing constructive criticism, and (v) organizing online discussions and collaboration between students and lecturers and librarians.   Keyword:  ChatGPT, Academic productivity, AI, Artificial Intelligence ------------------------------------- CHATGPT: ANTARA PELUANG DAN TANTANGAN DALAM MENINGKATKAN PRODUKTIVITAS AKADEMIK ABSTRAK Pendahuluan: CHATGPT, salah satu inovasi baru Open AI yang sukses, telah membuat kagum banyak orang di seluruh dunia. ChatGPT membantu penelitian ilmiah dalam pembelajaran dapat menjadi inovasi pendidikan yang bermanfaat bagi pelajar dan perguruan tinggi namun ChatGPT memiliki potensi dan ancaman. Tujuan Penelitian: memberikan gambaran mengenai peluang dan tantangan penggunaan chat GPT bagi pelajar/mahasiswa. Metode Penelitian: Studi Literatur, pendekatan kualitatif. Hasil Penelitian: Tantangan utama dan implikasi etis ChatGPT di pendidikan tinggi :1. Integritas Akademik 2. Gender dan Keberagaman 3. Aksesibilitas. Menavigasi Pergeseran Digital: Meningkatkan Kompetensi Digital dalam Pendidikan Kolaborasi. Manusia-AI dan pedagogi teknologi canggih: peluang untuk ChatGPT. Kesimpulan: ChatGPT dapat digunakan dalam pendidikan tinggi dan pelatihan, untuk (i) menetapkan sumber daya pengajaran dan rencana studi individual berdasarkan kebutuhan dan minat masing-masing peserta didik, (ii) membimbing peserta didik melalui pendidikan secara tepat waktu, (iii) menghasilkan materi pembelajaran yang menarik hal-hal seperti tes, tugas menarik, dan video interaktif, (iv) mendukung dosen dalam menilai hasil karya mahasiswa dan memberikan kritik yang membangun, dan (v) menyelenggarakan diskusi online dan kolaborasi antara mahasiswa dengan dosen dan pustakawan.   Kata Kunci: ChatGPT, Produktivitas Akademik, AI, Kecerdasan Buatan